Influence of training schedules on objective measures of sleep in adolescent academy football players - Brown, G. A.; Veith, S.; Sampson, J. A.; Whalan, M.; Fullagar, H. H. (The Journal of Strength and Conditioning Research, 2020)
Football academy settings may pose risks to adolescent athletes achieving sufficient sleep because of the contextual challenges these players face (e.g., psychosocial pressure, changes in training, competition, and academic stress). Given the importance of sleep to overall health as well as physical athletic development and injury risk, this study aimed to investigate whether differences in training schedules (morning vs. evening training sessions) affected objective measures of sleep in adolescent academy football (soccer) players. Twelve academy players (mean age 14.18 ± 1.36 years) wore an ActiGraph accelerometer on nights before, and nights of, training days in 2 separate weeks where morning (09:00-11:00 hours) and evening (18:00-20:00 hours) training occurred. Objective sleep parameters and training load data were collected. Night-time sleep periods were categorized as sleep preceding morning training, preceding evening training, or after evening training. One-way univariate and multivariate analyses of variance for repeated measures were performed to determine the impact of the training schedule on sleep. Significance levels were set at p < 0.05. The total sleep time was below the recommended guidelines (<8 hours) across conditions. A large significant effect of the training schedule on time attempted to fall asleep (p = 0.004, effect size [ES] = 0.40) and time of sleep (p = 0.003, ES = 0.41) was present, with post-evening sessions resulting in the latest times. Overall, the players' sleep behavior was resilient to changes in training schedules. However, the low sleep durations (and potential risks to physical performance/injury) suggest that sleep education coupled with practical interventions are required in this cohort.